ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN, LOKASI, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Taman Joglo Cafe Semarang) - Nurcahyo, Brian Hesmu; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
This research was conducted as a decline in sales at Taman Joglo Cafe for several months, so we have to know what factors that influence the purchase decision . This study aims to determine the effect of price perception, service quality, location, and word of mouth on purchase decision on Taman Joglo Café Semarang and which ones have the most impact.The research data was collected from 100 consumers Taman Joglo Café Semarang. Sampling in this study using non-probability sampling technique . The analysis used in this study is multiple regression analysis . Before multiple regression analysis also do validity and reliability testing and classical assumption testing.And after that also do the hypothesis testing and coefficient of determination. The results of the study found that the following regression equation: Y = 0,745  + 0,363  + 0,217 + 0,116 .Regression analysis showed variable of price perception, service quality, location, and word of mouth have a positive influence to the purchase decision. The most influential variable was price perception, followed by service quality, location and word of mouth. The analysis result using t test showed that price perception, service quality, location, and word of mouth individually have a significant influence on purchasing decisions. This equation model had F value of 67.784 with a significance level of 0.000. The analysis result using coefficient of determination was discovering about 73,0% variable of purchasing decision can be summarized by the variant of variable price perception, service quality, location, and word of mouth, whilst 27.0% summarized by other variable which unexplained in this research.